Thyroid-stimulating immunoglobulins as measured in a reporter bioassay are not detected in patients with Hashimoto’s thyroiditis and ophthalmopathy or isolated upper eyelid retraction - Wall JR (Dove Medical Press, 2014)
Jack R Wall,1 Hooshang Lahooti,1 Ilhem El Kochairi,1 Simon D Lytton,2 Bernard Champion1 1Department of Medicine, the University of Sydney, Penrith, NSW, Australia; 2SeraDiaLogistics, Munich, Germany Abstract: Although ophthalmopathy is mainly associated with Graves’ hyperthyroidism, milder eye changes are also found in about 25% of patients with Hashimoto’s thyroiditis (HT). The recent finding of negative thyrotropin receptor (TSHR) antibodies, as measured in the Thyretain™ thyroid-stimulating immunoglobulin (TSI) reporter bioassay, in patients with euthyroid Graves’ disease raises the possibility that TSHR antibodies are not the cause of ophthalmopathy in all situations. Here, we have tested serum from patients with HT with and without ophthalmopathy or isolated upper eyelid retraction (UER) for TSHR antibodies, using the TSI reporter bioassay and collagen XIII as a marker of autoimmunity against the orbital fibroblast. Study groups were 23 patients with HT with ophthalmopathy, isolated UER, or both eye features and 17 patients without eye signs. Thyretain™ TSI results were expressed as a percentage of the sample-to-reference ratio, with a positive test being taken as a sample-to-reference ratio of more than 140%. Serum collagen XIII antibodies were measured in standard enzyme-linked immunosorbent assay. TSI tests were positive in 22% of patients with HT with no eye signs but in no patient with eye signs. In contrast, TSI tests were positive in 94% of patients with Graves’ ophthalmopathy. Tests were negative in all normal subjects tested. Collagen XIII antibodies were detected in 83% of patients with ophthalmopathy, UER, or both eye features, but in only 30% of patients with no eye signs. Our findings suggest that TSHR antibodies do not play a major role in the pathogenesis of ophthalmopathy or isolated UER in patients with HT. Moreover, the role of TSHR antibodies in the development of ophthalmopathy in patients with Graves’ disease remains to be proven. In contrast, collagen XIII antibodies appear to be a good marker of eye disease in patients with HT. Keywords: Hashimoto’s thyroiditis, ophthalmopathy, upper eyelid retraction, TSH receptor antibodies, collagen XIII